Pengaruh Modal Sendiri dan Modal Pinjaman Terhadap Sisa Hasil Usaha Pada KPRI Kowarsda - Isdiensari, Endrica (COMPETITIVE, 2023)
This study aim to analyze the influence of the number of own capital, external capital on the remaining Bussiness Result (SHU) in cooperative in Sukabumi for period 2017-2020. This study uses a quantitative approach. This study taking place in KPRI Kowarsda Sukabumi The subject used in this study is an annual period of 2017-2020. The method used in this study ia s panel data regression analysis moel that is processed using SPSS 25 software. Based on the result of the analysis it is shown that the variable independent one (X1) own capital and variable indepent two (X2) have a positive and significant effect on variable dependent SHU.